Jordan : Strategy for Adjustment and Growth - Mansur, Ahsan (Occasional Papers; Occasional Paper ;, 1996)
The paper analyzes the major progress Jordan has made in recent years in macroeconomic stabilization and the transformation of its economic structure. It discusses recent economic developments, macroeconomic policies, and structural reforms and examines the factors underpinning growth, including structural reforms in key areas such as public finance, the financial system, the trade and exchange regime, Jordan's external debt-management strategy, and the dynamics of the public debt and its sustainability.